The Revival of Pragmatism New Essays on Social Thought, Law, and Culture - Alan, Wolfe; David, Bromwich; David, Luban; Dickstein, Morris; Fish, Stanley; Giles, Gunn; Hans, Joas; James, Kloppenberg; Jameson, Fredric; John, Diggins; Louis, Menand; Michel, Rosenfeld; et al. (Post-Contemporary Interventions, 1998)
Although long considered the most distinctive American contribution to philosophy, pragmatism-with its problem-solving emphasis and its contingent view of truth-lost popularity in mid-century after the advent of World War II, the horror of the Holocaust, and the dawning of the Cold War. Since the 1960s, however, pragmatism in many guises has again gained prominence, finding congenial places to flourish within growing intellectual movements. This volume of new essays brings together leading philosophers, historians, legal scholars, social thinkers, and literary critics to examine the far-reaching effects of this revival.As the twenty-five intellectuals who take part in this discussion show, pragmatism has become a complex terrain on which a rich variety of contemporary debates have been played out.